A Cover of Rhoma Irama’s Song “Rambate Rata Hayo” by the Dangdut Group Gita Bayu Reborn Gresik: An Analysis of the Arrangement and Song Structure - Ade Candra Bima Sakti (Universitas Negeri Surabaya, 2026)
This study examines the cover version of Rhoma Irama’s “Rambate Rata Hayo” by the Gita Bayu Reborn Dangdut Group from Gresik, focusing on its arrangement and form. The author employed a qualitative descriptive method using interviews. This study aims to analyze the song structure and arrangement of the cover version of Rhoma Irama’s “Rambate Rata Hayo” by the Gita Bayu Reborn Dangdut Group. This study concludes that the song “Rambate Rata Hayo” by Rhoma Irama, as performed by the Gita Bayu Reborn Dangdut Group from Gresik, is structured in a dangdut rock band format consisting of 128 measures in the key of (2#, do = D) at a tempo of 105, with a 4/4 time signature, and utilizes a distorted guitar effect that brings the rock-dangdut atmosphere to life. Furthermore, the arrangement of this song differs from the original in its structure, key, instruments, and playing style, resulting in an engaging song that has gained popularity with the public.